Influence of Different Acupuncture Method on Points Transcutaneous CO2 Emission - 黄涛 王瑞红 张维波 田宇瑛 王广军 徐一慧 韩彬 黄鑫 (Journal of acupuncture and tuina science, 2008)
Objective To observe the influence of transcutaneous CO 2 emission (TCE) at points on the meridian or beside the meridian after different stimulations like acupuncture De-qi, sham acupuncture, study the correlation between acupuncture De-qi and local energy metabolism through TCE. Methods Twenty healthy volunteers (male 8, female 12, average age 29 years old) were selected. Before, during and after five different acupuncture Neiguan (PC 6), the TCE was measured at Quze (PC 3), point A [at the lower one fourth of line between Tianquan (PC 2) and Quze (PC 3)], point B [at the middle of line between Ximen (PC 4) and Quze (PC 3)], point C (2 cm ulnar side point A) and point D (2 cm ulnar side point B) with a high sensitive CO 2 instrument (Frewil-Q.F., made in China). The measure results were compared. Results The comparison on value of TCE before and after the acupuncture, in Sham acupuncture and shallow acupuncture groups, it increased in all five points; in De-qi acupuncture group, there are significant increase on point A, point B, and Quze (PC 3), it has statistic significance, but there are no significant increase on point C and D. After Ximen (PC 4) or Daling (PC 7) were pressed to block Neiguan (PC 6), the value of TCE on Quze (PC 3), point A and point B were decreased during acupuncture Neiguan (PC 6), and increased after the block was removed, but there was no significant difference. Conclusion Sham acupuncture has also some effects on body, it can increase energy metabolism of local skin, it may be the reason that shallow acupuncture without qi arriving can obtain clinical efficacy. The operation method of traditional qi arriving acupuncture can increase energy metabolism of relevant meridian skin, mechanical press can reduce this effect.